Transformasi Hukum Operasi Tangkap Tangan Dalam Penindakan Tindak Pidana Korupsi - Amiruddin, Sulaiman; Marsudianto, Dwi Nugroho; Yudianto, Bambang; Herman, KMS (JURNAL RETENTUM, 2023)
This study examines the need for more detailed regulations regarding the implementation of Hand-Catching Operations (OTT) in eradicating corruption in Indonesia. Although the authority of the Corruption Eradication Commission (KPK) to carry out OTT has been regulated in Law Number 30 of 2002, the regulation is still general and does not explain the procedures and limitations of authority in its implementation. This study aims to analyze the need for clearer regulations regarding the procedures for implementing OTT, initial evidence requirements, arrest time limits, and protection of human rights. The method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that detailed regulations regarding OTT are needed to prevent abuse of authority, increase accountability, and ensure that the implementation of OTT is in accordance with the principles of legality and due process of law. The main recommendation of this study is the need for a more assertive determination of authority, clear procedures, and strengthening the implementation of the principle of legality, especially related to electronic evidence, to support the effectiveness of fair and transparent corruption eradication.